Web-Based Remote Monitoring And Controlling System Using Embedded Web Server - Shafie@Musa, Siti Mariam (2002)
The World Wide Web (WWW) has established itself as a strong medium for distributed computing: a network user interface that is powerful and platform independent. As embedded systems become more prevalent. the need for connectivity of the devices or appliances to the WWW becomes inevitable. This thesis proposed a system that can control and monitor appliances or devices through the web by implementing embedded web server called SitePlayer web server. The embedded web server is used to serve static or dynamic information requested by user through the standard web browser such as Internet Explorer and Netscape. Web page which contains dynamic data that acts as a user interface is designed using HTML language. These Web pages is downloaded into the SitePlayer web server through the SiteLinker Program. The downloading process is done through the Ethernet line. From the web page, user from remote site can open a link to control or monitor the status of the application at local site using Web browser such as Internet Explorer.